Contemporary Native Women: Role Flexibility and Politics - Miller, Bruce G. (Anthropologica, 2022)
Some recent efforts to reconceptualize contemporary Native gender systems (1) argue that tribal and band political life is best understood by reference to social formations other than gender systems and (2) rely on poorly defined notions of one feature of the gender system, role flexibility. This article argues that these two issues are connected; differences in role flexibility by sex help channel the political participation of men and women. Several notions of role flexibility, each with different properties and implications for women's political role, are employed in the literature. A comparative framework of role flexibility is constructed, building on the work of Kopytoff (1991), and ethnographic examples are used to build the case that the analysis of gender (including role flexibility) is important in understanding Native women's recent successes in politics.